The Relationship Between Adults, Elderly, and Smoking History With The Incidence Of Adhesive Capsulitis Shoulder - Malik, Fika Asdayanti; Susanty, Sri; Rustam, Muhammad (Poltekkes Kemenkes Surakarta, 2024)
Background: The pathological condition known as Adhesive Capsulitis Shoulder (ACS) is characterised by the excessive production of fibrotic tissue, resulting in the rigidity of the capsule of the glenohumeral joint. These factors encompass age, gender, extended immobilisation of the shoulder region, tobacco use, and more variables. The primary objective of this study is to investigate the correlation between adults, older people, and smoking history in relation to the prevalence of adhesive capsulitis shoulder at the Orthopaedic Poly of Indonesia. Methods: The present investigation employs an observational analytical design, utilising a case-control methodology. The study examined the relationship between two independent variables: age (specifically adults and older people) and smoking history. The dependent variable under investigation was adhesive capsulitis in the shoulder. The purposive selection technique was employed to choose a sample consisting of 94 cases of ACS events and 94 controls who did not experience any ACS events. A statistical test known as the Odds Ratio (OR) was conducted to analyse the data. Results: The test results indicate that age (OR <1; OR = 0.178, 90% CI 0.092–0.346) and smoking history have a significant impact on the incidence of adhesive capsulitis shoulder at the Orthopaedic Poly of Indonesia. Additionally, both variables have a value (OR <1; OR = 0.501, 90% CI 0.294–0.793). Conclusion: The findings of this study indicate a correlation between age (adults and older adults), smoking history, and the occurrence of adhesive capsulitis in the shoulder at Orthopaedic Poly Indonesia.